Bioresorbable Electronics: Mechanically Milled Irregular Zinc Nanoparticles for Printable Bioresorbable Electronics (Small 17/2017). Issue 17 (2nd May 2017) - Mahajan, Bikram K.; Yu, Xiaowei; Shou, Wan; Pan, Heng; Huang, Xian
Abstract : In article number1700065, by Heng Pan, Xian Huang, and co‐workers, a novel process to achieve bioresorbable electronic devices using ball milled zinc nanoparticles is demonstrated. The obtained nanoparticles can be printed directly on flexible and bioresorbable substrates, which can be sintered using a flash Xe lamp to form conductive circuits. This approach may lead to mass fabrication of bioresorbable electronic devices using steps compatible to printable electronics.